ANTI-HIPERCHOLESTEROLEMIA OF ANREDERA CORDIFOLIA IN HYPERCHOLESTEROLEMIA RAT WISTAR THROUGH DECREASE OF MALONDIALDEHYDE AND 8-HYDROXY-DIGUANOSINE - Wahjuni, S. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol 8 No 1 (2014): IJBS Vol8 No1, 2014)
High cholesterol diet leads to increase of plasma cholesterol and subsequently will end up with hypercholesterolemia. Ignorance of healthy food and lacks of activity are the trend of modern life style. These conditions exacerbated the incidence of hypercholesterolemia in either developed or developing countries. This research aims to determine potential of anredera cordifolia leafs extracts as an anti-hypercholesterolemia by lowering of malondialdehyde (MDA) and 8-hydroxy-diguanosine (8-OHdG) blood levels in hypercholesterolemia Wistar Rat. This is an experimental study applied post only control group design. A number of 15 male wistar rats were used in this study. Rats were randomly divided into 3 groups, i.e. negative control group (C1), positive control group (C2) and anredera cordifolia leaf extract at dose of 100 mg/kg BW group (T). MDA was determined based on malondialdehyde assay (NWLSS TM ).  8-OHdG was determined based on oxidative DNA Damage (Cell Biolabs, Inc). The mean difference between control and treatment was assessed by applying ANOVA and consider significant at p < 0.05. In this study, we observed that there were a significant of MDA and 8-OHdG levels between group C1 and T; C2 and T within p < 0.05. This result indicates anredera cordifolia leafs extract has an ability to inhibit hypercholesterolemia in wistar rat fed with high cholesterol diet.
Keywords: Anredera cordifolia, hypercholesterolemia, MDA, and 8-OHdG.